Tari Tradisional dalam Lingkup Pendidikan (2010-2020): sebuah Analisis Bibliometrik - Fatmawati, Yani; Julia, J.; Gusrayani, Diah (Jurnal Pena Ilmiah, 2021)
This study analyzes the development of journal articles on the topic of traditional dance for the period 2010-2020 using a bibliometric research design. Research with bibliometric studies is conducted using four stages, namely data collection using Publish or Perish (PoP) software through Scopus, filtering bibliographic metadata, check the completeness of the bibliography with EndNote online, and bibliographic analysis with the VOSviewer application. The results of the bibliometric study obtained six findings, as follows (1) The most widely used title term is â€œtraditional danceâ€; (2) Abstract terms which have the highest number of links are â€œtraditional danceâ€; (3) The most used keywords are â€œtraditional danceâ€; (4) The writer who has the highest level of collaboration with other writers, namely Filippou, f; (5) The most frequent citations are in 2011 and the least occurred in 2020; and (6) The most publication development occurred in 2020 and the least occurred in 2016.